2019
DOI: 10.3390/en12122400
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Insulation Solution that Leads to Lower CO2 Emissions during the Construction Phase of a Building

Abstract: The characteristics of the envelope of a building determine, together with other factors, its consumption of energy. Additionally, the climate zone and insulation material may vary the minimum insulation thickness of walls and roofs, making it different, according to cooling down or warming up the home. Spanish legislation establishes different maximum values for energy demand according to different climate area both for heating and for cooling. This paper presents the results of a study that determines the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
0
4
0
2
Order By: Relevance
“…The energy efficiency of buildings has been analyzed in most Southern European countries, such as Greece [67], Italy [68], Portugal [69] and Turkey [70], as well as Spain [32,71,72]. However, these studies use cases of multifamily buildings by climatic zones or located in a specific geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…The energy efficiency of buildings has been analyzed in most Southern European countries, such as Greece [67], Italy [68], Portugal [69] and Turkey [70], as well as Spain [32,71,72]. However, these studies use cases of multifamily buildings by climatic zones or located in a specific geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, communities have committed to reducing carbon emissions by enacting various sustainable measures. Looking at the life cycle stages of a building, it is clear that buildings' lifespan ranges from 50 to 100 years; therefore, buildings must be resilient enough to withstand future impacts [69]. Sustainability in construction separates the life cycle into four different stages: the production stage, the construction stage, the use stage, and the end of life stage.…”
Section: Embodied Carbon In Buildingsmentioning
confidence: 99%
“…The GWP is the extent of global warming impacts of different gases [78]. In a study determining the insulation of various materials, expanded cork was shown to reduce the amount of carbon emissions during the construction phase and lower the GWP overall while providing the optimal thickness needed for heating and cooling [69].…”
Section: Reducing Embodied Carbon In Buildingsmentioning
confidence: 99%
“…Los estudios de renovación de la envolvente térmica de los edificios se centran en encontrar la solución óptima en cuanto a costes (Fernandes et al, 2021), pero no se considera el impacto en la posibilidad de perder superficie útil (Bastante-Ceca et al, 2019). Este trabajo presenta una herramienta de desarrollo VBA de MS Excel para evaluar el impacto de aplicar un sistema de aislamiento interno en la superficie útil y la demanda energética.…”
Section: Introductionunclassified